Análisis económicos de las importaciones de Denim en Colombia durante 2010- 2020 - Dominguez, Leydi Yohana (Universidad Antonio Nariño, 2022)
This research presents an overview of the importance of the textile sector for the Colombian economy, so it was proposed as a general objective to analyze at an economic level the impact of denim imports in Colombia during the years 2010 to 2020, for which a description of the behavior of denim imports in the last decade made by the national industry is made, in order to then compare the impact of the import of denim in the Colombian textile industry with the behavior of exports of products derived from the input, followed by a systematic exploration of the denim production of the textile sector in Colombia, between the years 2010 to 2020.